THE LUDIC IMPULSE IN THE THEATRIC GAME THROUGH MIMICRY AND ILÏNX (Fiep Bulletin - online, 2014)
This study proposes the development of the body language - dance by motivation of the imagination, through roleplaying games, in the School's Physical Education. The methodological support of the research, within the scope of the imaginary, bases its theoretical grounding on the analysis of the speech, explained by Callois' (1990) mimicry and ilïnx categories, trying to reach, through the social dimension, the expansion and democratization of the dance within the school sphere.
Keywords: dance; role playing games; ludic impulse; mask; possession